If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -10 = -2(2x + 5) Reorder the terms: -10 = -2(5 + 2x) -10 = (5 * -2 + 2x * -2) -10 = (-10 + -4x) Add '10' to each side of the equation. -10 + 10 = -10 + 10 + -4x Combine like terms: -10 + 10 = 0 0 = -10 + 10 + -4x Combine like terms: -10 + 10 = 0 0 = 0 + -4x 0 = -4x Solving 0 = -4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4x' to each side of the equation. 0 + 4x = -4x + 4x Remove the zero: 4x = -4x + 4x Combine like terms: -4x + 4x = 0 4x = 0 Divide each side by '4'. x = 0 Simplifying x = 0
| 36/6*6+6-4 | | -2r-9=-3r-6 | | 8x+10=-118 | | A=qt+q | | 200x-2x^2=4250 | | .25x+.05(6-x)=.10(-5) | | w+0.06w=13.25 | | -12=c/4 | | -5-12=-2 | | 9-8*2/4+9 | | 3(x+2)=1.5(4+2x) | | 1.14p=57 | | (x^2/5)^5/6 | | y-(-8)=5/6(x-5) | | X^3-10=54 | | (3/7)*x+8=11 | | x/(x^2+2x-3)+1/(1-2x+x^2) | | 9-8x2/4+9 | | 14(x+7)=3(x-4) | | -1.5t+5+3t=6 | | -n^2-34n-33= | | 4x+32=-2x+2 | | m-8=2m | | y-(-6)=2/3(x-4) | | 93=2x+3(4x-11) | | 3q*16=2q+12 | | ab^2+4b^2=0 | | -2x+5y=30 | | 3-x=5+3x | | 5x/2+12=99 | | 20=2(7x-4) | | 4x-10=6x+28 |